Perceived Organizational Culture and Violence Prevention Climate among Healthcare Workers: Cross-Sectional Associations in Zonguldak, Türkiye - Ayhan Terzibas; Yusuf Ocel (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Workplace violence is a major occupational and public health concern in healthcare settings. Although organizational culture and violence prevention climate have been examined in previous studies, limited evidence exists on how different perceived organizational culture types are associated with specific dimensions of violence prevention climate among healthcare workers. Methods: This analytical cross-sectional study was conducted with 388 healthcare workers employed in public and private healthcare institutions in Zonguldak, Türkiye. Data were collected using a survey form including validated organizational culture and violence prevention climate scales. Descriptive statistics, confirmatory factor analysis, common method bias assessment, discriminant validity tests, correlation analysis, independent-samples t-tests, and simultaneous regression analyses were performed using SPSS and AMOS. Results: The measurement models showed acceptable reliability and validity. Common method bias was not considered a severe concern, and additional discriminant validity analyses supported the empirical distinctiveness of highly correlated constructs. Simultaneous regression analyses indicated that clan, market, and hierarchy cultures were positively associated with policies and procedures, whereas adhocracy culture was not significant. All four culture types were positively associated with practices and responses. For pressure for unsafe practices, clan and hierarchy cultures showed negative associations, market culture was not significant, and adhocracy culture showed a positive association. Public healthcare workers reported higher scores for organizational culture, policies and procedures, and practices and responses than private healthcare workers, while pressure for unsafe practices did not differ significantly by institution type. Conclusion: The findings indicate perceptual associations between organizational culture and violence prevention climate among healthcare workers. Because the study used a cross-sectional design, convenience sampling, and self-reported data, the results should not be interpreted as causal evidence. Strengthening organizational culture may be considered an evidence-informed strategy for supporting violence prevention climate, but future longitudinal and multi-source studies are needed.